Detection of submillimeter-wave [C I]emission in gaseous debris disks of 49 Ceti and β Pictoris. Issue Volume 13:Issue S332(2017) (4th September 2018) - Higuchi, Aya E.; Sato, Aki; Tsukagoshi, Takashi; Sakai, Nami; Iwasaki, Kazunari; Momose, Munetake; Kobayashi, Hiroshi; Ishihara, Daisuke; Kaneda, Hidehiro; Yamamoto, Satoshi
Abstract: We have detected [C I] 3 P 1 – 3 P 0 emissions in the gaseous debris disks of 49 Ceti and β Pictoris with the 10 m telescope of the Atacama Submillimeter Telescope Experiment, which is the first detection of such emissions. The line profiles of [C I] are found to resemble those of CO( J =3–2) observed with the same telescope and the Atacama Large Millimeter/submillimeter Array. This result suggests that atomic carbon (C) coexists with CO in the debris disks, and is likely formed by the photodissociation of CO. Assuming an optically thin [C I] emission with the excitation temperature ranging from 30 to 100 K, the column density of C is evaluated to be (2.2 ± 0.2) × 10 17 and (2.5 ± 0.7) × 10 16  cm −2 for 49 Ceti and β Pictoris, respectively. The C/CO column density ratio is thus derived to be 54 ± 19 and 69 ± 42 for 49 Ceti and β Pictoris, respectively. These ratios are higher than those of molecular clouds and diffuse clouds by an order of magnitude. The unusually high ratios of C to CO are likely attributed to a lack of H2 molecules needed to reproduce CO molecules efficiently from C. This result implies a small number of H2 molecules in the gas disk; i.e., there is an appreciable contribution of secondary gas from dust grains.